Shortcomings in the Legal System on Securities in Vietnam - Nguyen Vinh Hung; Tran Cong Thinh; Dao Xuan Hoi (Jurnal Cita Hukum, 2022)
Nowadays, Vietnam’s stock market has had rapid growth and attracted an increasing number of investors. However, among various factors that affect the investors’ participation, psychological ones play a crucial role. In more than 20 years of development, the legal system on securities in Vietnam has exposed several limitations and inadequacies that result in inefficient operation of the stock market and unsafely for domestic and foreign investors. Therefore, the article will study the shortcomings of the legal system on securities of Vietnam, from that propose some solutions to ensure the safety of investors in Vietnam’s stock market participation. To research the psychological factors of stock investment in Vietnam, the authors choose to combine the method of collecting and analyzing information (data). The main research method used in this article is collecting secondary data from the collected data. In general, the article uses the synthesis of data from many sources of information that the author team can obtain and always analyzes tests, compares, evaluates to identify the important problems for studying. In addition, in order to approach the research subjects, the article also uses a combination of popular research methods of economic fields such as statistical method, comparative method, economic efficiency analysis method and descriptive method for the purpose of analyzing, evaluating and forecasting the psychological factors of securities investment affecting Vietnam’s stock market. According to the results authors have given two main groups of solutions: Dealing with inaccurate information that affects the transparency of the stock market; and building and perfecting Vietnam's securities legal system.